Respostas

2014-03-22T19:40:46-03:00
An = a1 + (n-1) . r          
a2 = 5 + (2-1) . 3 = 5 + 1.3 = 5 + 3 = 8
a3 = 5 + (3-1) . 3 = 5 + 2.3 = 5 + 6 = 11
a4 = 5 + (4-1) . 3 = 5 + 3.3 = 5 + 9 = 14
a5 = 5 + (5-1) . 3 = 5 + 4.3 = 5 + 12 = 17
a6 = 5 + (6-1) . 3 = 5 + 5.3 = 5 + 15 = 20

PA : ( 5 , 8 , 11 , 14 , 17 , 20 ) 
1 5 1
verdade esquece do 6 termo
*esqueci
2014-03-22T19:43:18-03:00
É simples é só somar o termo com a razão :
A1+R= 5+3= 8 segundo termo
A2+R= 8+3= 11 terceiro termo
A3+R= 11+3=14 quarto termo
A4+R=14+3= 17 quinto termo
A5+R=17+3= 20 sexto termo

PA(5,8,11,14,17,20)


Corrigi :D
Pronto, questão corrigida :)
:))